Microwave Assisted Synthesis of 2,4-Diphenyl-4H-chromen-5-one Using ZnCl2/Montmorillonite K-10 - Swapnil R. Sarda; Ujwala S. Maslekar; Wamanrao N. Jadhav; Rajendra P. Pawar (E-Journal of Chemistry)
α, β-Unsaturated carbonyl compounds and 1, 3-cyclohexanedione under microwave irradiation in the presence ZnCl2/montmorillonite K-10 offers the corresponding 2,4-diphenyl-4H-chromen-5-one in excellent yield. Catalyst is recycled and reused for several times